Choroidal thickness as a biomarker of systemic inflammation in patients with polymyalgia rheumatica - Trives-Folguera, Laura; Muñoz-Fernández, Santiago; Esteban-Ortega, María del Mar; Coca-Serrano, Raquel; Cobo-Ibañez, Tatiana; Vergara-Dangond, Cristina; Romero-Bogado, Liz; de la Cámara-Fernández, Isabel; Richi, Patricia; Paredes, María Beatriz; Esteban-Vazquez, Ana; Acosta, Ana Valeria; et al. (Frontiers in Medicine, 2025)
ObjectiveChoroidal thickness (CT) varies with systemic inflammatory activity in diseases such as spondyloarthritis, suggesting its potential role as a biomarker. This study aimed to evaluate changes in CT in patients recently diagnosed with Polymyalgia Rheumatica (PMR) who are undergoing corticosteroid therapy, over a six-month follow-up period.MethodsIt is a prospective, observational, longitudinal pilot study including 20 patients with recent PMR diagnosis from two centres. All participants met PMR classification criteria. Participants underwent three visits: at diagnosis (baseline), at 3 and 6 months after starting corticosteroids. Each visit included physical examination, musculoskeletal ultrasound (MSK US) of shoulders and hips, blood tests including C-reactive protein (CRP) and erythrosedimentation rate (ESR) and CT measurement by optical coherence tomography (OCT). Disease activity was assessed using the PMR Activity Score (PMR-AS) and its imputed version.ResultsMean baseline CT was 242.10 ± 79.05 μm. Choroidal thickness decreased significantly after 3 months (229.85 ± 79.01 μm, p = 0.017) and after 6 months (220.37 ± 75.96 μm, p = 0.014) of corticosteroid treatment. We found a significant decrease in all laboratory and clinical parameters. Concordance between CT, CRP, and PMR-AS was 95%. Rotator cuff pathology does not appear to influence on evolution of MSK US bicipital tenosynovitis inflammatory findings neither in pain.ConclusionWe found that CT was high in patients with recent diagnosis of PMR and decreases significantly after 3 and 6 months of corticosteroid therapy. There is a 95% of concordance between CT and CRP as well as between CT and PMR activity scores. Our findings suggest that CT is useful as a noninvasive, imaging-based biomarker of systemic inflammation in patients with PMR. More studies are needed to confirm these preliminary results.